2007
DOI: 10.1007/s00484-007-0094-7
|View full text |Cite
|
Sign up to set email alerts
|

Long-term trends in first arrival and first egg laying dates of some migrant and resident bird species in northern Italy

Abstract: Climate change is affecting the phenology of seasonal events in Europe and the Northern Hemisphere, as shown by several studies of birds' timing of migration and reproduction. Here, we analyse the long-term (1982-2006) trends of first arrival dates of four long-distance migratory birds [swift (Apus apus), nightingale (Luscinia megarhynchos), barn swallow (Hirundo rustica), and house martin (Delichon urbicum)] and first egg laying dates of two migrant (swift, barn swallow) and two resident species [starling (St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
36
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 54 publications
6
36
0
Order By: Relevance
“…Migration timing can be modified by evolutionary processes, because arrival time affects the time of breeding (Turner 1982, Tryjanowski et al 2004, Newton 2007, Rubolini et al 2007). The link between spring migration and breeding is probably due to changes in food sources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Migration timing can be modified by evolutionary processes, because arrival time affects the time of breeding (Turner 1982, Tryjanowski et al 2004, Newton 2007, Rubolini et al 2007). The link between spring migration and breeding is probably due to changes in food sources.…”
Section: Discussionmentioning
confidence: 99%
“…Most likely, migration is faster because environmental conditions during migration have improved (Huin & Sparks 1998, Gordo et al 2005, Rubolini et al 2007). However, it appears clear that sand martins are arriving now considerably earlier than barn swallows, seem more temperature responsive, and appear to have had a greater supra-temperature change.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of the NAO on local weather are observable throughout the year, but this index shows its greatest level of variability during wintertime, when the air masses that cross the Atlantic embed their highest energy content (Stenseth et al 2003). For these reasons, the NAO is mainly considered a winter climatic index, although it may influence weather conditions of western Europe (Hurrell and van Loon 1997;Stenseth et al 2003) and the Mediterranean basin (Rubolini et al 2007;Cañellas et al 2010) all over the year. In the Mediterranean, the influence of the NAO on local weather has been demonstrated in relation to air and sea temperatures, precipitations and river discharges (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies that have investigated interannual variation in first or mean arrival dates at the breeding grounds in relation to ecological (mainly thermal) conditions at destination upon arrival or along the migration route have demonstrated that in years with relatively high spring temperatures migrants arrive earlier (Huin & Sparks 1998, Loxton et al 1998, Sokolov et al 1998, Sparks & Mason 2001, Tryjanowski et al 2002, Croxton et al 2006, Gordo & Sanz 2006, Rubolini et al 2007b, Sparks & Tryjanowski 2007. Whatever the mechanisms that allow birds to tune their arrival schedule based on current conditions 100s or 1000s of kilometres ahead, these studies suggest that birds can balance the ecological or socio-sexual costs and benefits of early departure from the wintering areas and arrival at the breeding grounds.…”
Section: Introductionmentioning
confidence: 99%